Dietary Clostridium butyricum Improves Growth Performance and Resistance to Ammonia Stress in Yellow Catfish (Pelteobagrus fulvidraco). (11th June 2022) - Li, Peijia; Hou, Dongqiang; Zhao, Hongxia; Wang, Hairui; Peng, Kai; Cao, Junming
Abstract : The effects of dietary Clostridium butyricum (CB) on growth performance, intestinal morphology, tight junction proteins, and immune-related gene mRNA levels in Pelteobagrus fulvidraco were investigated. The fish were fed with diets containing 0 (control, CB0), 4.8 × 10 6 (CB1), 4.5 × 10 7 (CB2), 5.1 × 10 8 (CB3), and 3.6 × 10 9 (CB4) CFU/kg Clostridium butyricum for 56 days followed by a 72 h ammonia challenge. The results showed that significantly higher final weight, specific growth rate, body length, and intestinal weight were observed in fish fed with CB diets (P < 0.05 ). The fish fed with CB1, CB2, and CB3 diets had significantly higher intestinal length, propionic acid concentration, and alkaline phosphatase activity and significantly lower feed conversion ratio than those in CB0 (P < 0.05 ). Significantly higher concentrations of butyric acid and valeric acid and significantly lower malondialdehyde content were observed in CB4 than in CB0 (P < 0.05 ). Intestosomatic index, villus length, villus width, intestinal protease, Na + /K + -ATPase, and creatine kinase activities were significantly increased in CB2 or CB3 than in CB0 (P < 0.05 ). Fish in CB2 or CB3 had significantly lower content of interleukin 1 β and interleukin 6 and relative expression of interleukin 1 ( Il-1 ), interleukin 8 (Il-8 ), and nuclear transcription factor-κB ( Nf-κb ) compared to that in CB0 (P < 0.05 ). Dietary CB significantly decreased the relative expression of myosin light chain kinase ( Mlck ) ( P <0.05). Significantly higher relative expressions of claudin-1, zonula occludens protein-1, and occludin were observed in CB2, CB3, and CB4 compared to CB0 (P < 0.05 ). Fish in CB0 had higher CMR than that in CB2, CB3, and CB4 under ammonia nitrogen stress for 48 and 72 h (P < 0.05 ). Dietary Clostridium butyricum improved growth performance and resistance to ammonia stress in yellow catfish by increasing intestinal short-chain fatty acid (SCFA) productions, upregulating genes encoding tight junction proteins, downregulating transcription of proinflammatory factors Il-1 and Il-8, and inhibiting the Mlck/Nf- κ b signaling pathway.